2018
DOI: 10.5210/ojphi.v10i3.9487
|View full text |Cite
|
Sign up to set email alerts
|

eHealth literacy and general interest in using online Health information: a survey among patients with dental diseases

Abstract: ObjectivesThe aim of the study is to explore the eHealth literacy and general interest in using eHealth information among patients with dental diseases.MethodsA total of 171 patients with dental diseases completed the survey including the eHEALS. The effect of participants' age, gender and education on eHealth literacy was assessed. Spearman’s correlation coefficient was also used to assess the correlation between the importance of access to health information and the usefulness of the internet for decision-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
3
17
1
Order By: Relevance
“…This finding may be since compared to middle adults, access to digital media is easier for young adults and they are more experienced in surfing the internet (7). This finding are in line with a study results on eHealth literacy level of Greek citizens as well as the results of a study on eHealth literacy of dental patients [26,44]; however, some other studies did not find this relationship to be significant [21,42]. According to the present findings, further studies are required to ascertain the relationship between age and eHealth literacy.…”
Section: The Relationship Between the Study Variables And Ehealth Litsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding may be since compared to middle adults, access to digital media is easier for young adults and they are more experienced in surfing the internet (7). This finding are in line with a study results on eHealth literacy level of Greek citizens as well as the results of a study on eHealth literacy of dental patients [26,44]; however, some other studies did not find this relationship to be significant [21,42]. According to the present findings, further studies are required to ascertain the relationship between age and eHealth literacy.…”
Section: The Relationship Between the Study Variables And Ehealth Litsupporting
confidence: 86%
“…A poor level of eHealth literacy was also reported in similar studies conducted on different groups, including the students [22] and patients referring to a military hospital [41]. Nonetheless, a study conducted on dental patients showed a good level of eHealth literacy among this group [26]. Further studies on different groups of the population are thus necessary.…”
Section: Ojphimentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, in this study, there was a positive correlation between the combination of both measures and education. Education level affects eHEALS via online search of health information (51). There are two Iranian studies that reported patients' eHealth literacy was related to their education level, but some other studies (52,53) failed to show this association.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] In addition, use of the Internet has increased people's awareness and knowledge about medical and health issues and has helped them to participate more in their health-care activities by making informed decisions. [ 5 ] The Internet is a powerful platform to change people's lifestyles and how people deal with health issues[ 6 ] and also has been shown to be a great hopeful source without changing health information. From 2000 to 2016, Internet penetration has grown by 900%.…”
Section: Introductionmentioning
confidence: 99%